The influence of COVID-19 related psychological and demographic variables on the effectiveness of e-learning among health care students in the southern region of Saudi Arabia - Sirajudeen Shaik Alavudeen; Vigneshwaran Easwaran; Javid Iqbal Mir; Sultan M. Shahrani; Anas Ali Aseeri; Noohu Abdullah Khan; Ahmed Mohammed Almodeer; Abdulaziz Abdullah Asiri (Saudi Pharmaceutical Journal, 2021)
Background: E-learning is a modern and flexible mode of education and is being used as an alternative to conventional mode of education during the ongoing COVID-19 pandemic. However evidence suggests that effectiveness of e-learning is influenced by many prevailing factors. Methods: A cross sectional study aimed to evaluate health care students’ perception towards implementation of e-learning was conducted for a period of 4 months, from April 2020 to July 2020. Research instrument consisted of a self-designed, qualitative questionnaire with three domains was validated using field pretest method and administered among health care students of King Khalid University using social media platforms. Chi square test was used to estimate the effect of e-learning on various domains whereas linear regression analysis was used to find the association between subjects’ characteristics to overall domain scores. P value < 0.05 was considered significant. Results: Among 254 respondents 59.8% were males and 96.5% respondents were staying with their families.10.2% reported medically imposed quarantine for one or more family members. 59.8% reported that the online classes were commenced too early. 63.4% of the respondents reported that they had no previous experience. Poor network connectivity (32.3%) and unawareness about online platforms (29.9%), poor audio/video qualities (26.3%) were found as major barriers. Psychological stress, discipline of study, living status and quarantine history had a remarkable impact on the effectiveness of online education. Conclusion: Health care students are still cynical and are yet to embrace e-learning fully. Psychological distress, technical issues in association with accessibility, inexperience and unpreparedness were found to be main barriers that limited student acceptance of e-learning.